Nature Articulations in Norwegian Advertising Discourse: A Depoliticized Discourse of Climate Change. Issue 6 (18th August 2018) - Kvidal-Røvik, Trine
ABSTRACT: This article deals with how nature is articulated in public discourse and more specifically how humans' relationship to nature is constructed via such articulations. Based on critical cultural analyses of ads presented in a Norwegian context, the article claims articulations of nature serve to a depoliticization of nature, which silence social differences and reduce environmental politics to individual moral action. Several rhetorical patterns of particular relevance to the articulation of nature are discussed, pointing out how disparate, sometimes conflicting, understandings of nature are rhetorically configured and aligned in ways that benefit a global market economy. There is a discursive distancing of nature and everyday life, even as nature remains valorized and very much central to national identity. This constrains citizens' political engagement and undermines understandings of how to govern nature.